Endoscopic full-thickness resection of T1 colorectal cancers: a retrospective analysis from a multicenter Dutch eFTR registry - Zwager, Liselotte W.; Bastiaansen, Barbara A. J.; van der Spek, Bas W.; Heine, Dimitri N.; Schreuder, Ramon M.; Perk, Lars E.; Weusten, Bas L. A. M.; Boonstra, Jurjen J.; van der Sluis, Hedwig; Wolters, Hugo J.; Bekkering, Frank C.; Rietdijk, Svend T.; Schwartz, Matthijs P.; Nagengast, Wouter B.; ten Hove, W. Rogier; Terhaar sive Droste, Jochim S.; Rando Munoz, Francisco J.; Vlug, Marije S.; Beaumont, Hanneke; Houben, Martin H. M. G.; Seerden, Tom C. J.; de Wijkerslooth, Thomas R.; Gielisse, Eric A. R.; Hazewinkel, Yark; de Ridder, Rogier; Straathof, Jan-Willem A.; van der Vlugt, Manon; Koens, Lianne; Fockens, Paul; Dekker, Evelien; on behalf of the Dutch eFTR Group (Endoscopy, 2022)
Background Complete endoscopic resection and accurate histological evaluation for T1 colorectal cancer (CRC) are critical in determining subsequent treatment. Endoscopic full-thickness resection (eFTR) is a new treatment option for T1 CRC < 2 cm. We aimed to report clinical outcomes and short-term results. Methods Consecutive eFTR procedures for T1 CRC, prospectively recorded in our national registry between November 2015 and April 2020, were retrospectively analyzed. Primary outcomes were technical success and R0 resection. Secondary outcomes were histological risk assessment, curative resection, adverse events, and short-term outcomes.Results We included 330 procedures: 132 primary resections and 198 secondary scar resections after incomplete T1 CRC resection. Overall technical success, R0 resection, and curative resection rates were 87.0 % (95 % confidence interval [CI] 82.7 %–90.3 %), 85.6 % (95 %CI 81.2 %–89.2 %), and 60.3 % (95 %CI 54.7 %–65.7 %). Curative resection rate was 23.7 % (95 %CI 15.9 %–33.6 %) for primary resection of T1 CRC and 60.8 % (95 %CI 50.4 %–70.4 %) after excluding deep submucosal invasion as a risk factor. Risk stratification was possible in 99.3 %. The severe adverse event rate was 2.2 %. Additional oncological surgery was performed in 49/320 (15.3 %), with residual cancer in 11/49 (22.4 %). Endoscopic follow-up was available in 200/242 (82.6 %), with a median of 4 months and residual cancer in 1 (0.5 %) following an incomplete resection. Conclusions eFTR is relatively safe and effective for resection of small T1 CRC, both as primary and secondary treatment. eFTR can expand endoscopic treatment options for T1 CRC and could help to reduce surgical overtreatment. Future studies should focus on long-term outcomes.